A novel deletion involving the first GNAS exon encoding Gsα causes PHP1A without methylation changes at exon A/B - BEREKET, ABDULLAH; DEMİRCİOĞLU, SERAP; GÜRAN, TÜLAY (My University, 2022)
© 2022Individuals affected by pseudohypoparathyroidism type 1A (PHP1A) display hyperphosphatemia and hypocalcemia despite elevated PTH levels, as well as features of Albright Hereditary Osteodystrophy (AHO). PHP1A is caused by variants involving the maternal GNAS exons 1–13 encoding the stimulatory G protein α-subunit (Gsα). MLPA and aCGH analysis led in a male PHP1A patient to identification of a de novo 1284-bp deletion involving GNAS exon 1. This novel variant overlaps with a previously identified 1438-bp deletion in another PHP1A patient (ref. Li et al. (2020) [13], patient 2) that extends from the exon 1 promoter into the up-stream intronic region. This latter deletion is associated with reduced methylation at GNAS exon A/B, i.e. the differentially methylated region (DMR) that is demethylated in most pseudohypoparathyroidism type 1B (PHP1B) patients. In contrast, genomic DNA from our patient revealed no evidence for an epigenetic GNAS defect as determined by MS-MLPA and pyrosequencing. These findings thus reduce the region, which, in addition to other nucleotide sequences telomeric of exon A/B, may undergo histone modifications or interacts with transcription factors and possibly as-yet unknown proteins that are required for establishing the maternal methylation imprints at this site. Taken together, nucleotide deletions or changes within an approximately 1300-bp region telomeric of exon A/B could be a cause of PHP1B variants with complete or incomplete loss-of-methylation at the exon A/B DMR. In addition, when investigating patients with suspected PHP1A, MLPA should be considered to search for structural abnormalities within this difficult to analyze genomic region comprising GNAS exon 1.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Pediatrik Endokrinoloji ve Metabolizma; Medicine; Health Sciences; Internal Medicine Sciences; Child Health and Diseases; Pediatric Endocrinology and Metabolism; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; PEDİATRİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; PEDIATRICS; Pediatrics; Family Practice; Fundamentals and Skills; General Health Professions; Pathophysiology; Pediatrics, Perinatology and Child Health; Internal Medicine; Assessment and Diagnosis; Medicine (miscellaneous); General Medicine; Pseudohypoparathyroidism type Ia (PHP1A); Albright hereditary osteodystrophy; Parathyroid hormone; Calcium; Phosphate; Gs-alpha; Gs alpha; Epigenetics; GNAS methylation; PSEUDOHYPOPARATHYROIDISM; PROTEIN; CYCLASE; GENE; Gsα